2019
DOI: 10.1002/lt.25454
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chronic Kidney Disease on Outcomes in Cirrhosis

Abstract: We hypothesize that the prevalence of chronic kidney disease (CKD) among patients with cirrhosis has increased due to the increased prevalence of CKD‐associated comorbidities, such as diabetes. We aimed to assess the characteristics of hospitalized patients with cirrhosis with CKD and its impact on renal and patient outcomes. The North American Consortium for the Study of End‐Stage Liver Disease (NACSELD) prospectively enrolled nonelectively admitted patients with cirrhosis and collected data on demographics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
52
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 41 publications
3
52
0
1
Order By: Relevance
“…They are therefore more susceptible to episodes of AKI and are less likely to have the renal reserve to recover from these episodes. This is supported by previous studies that demonstrated that those with a higher baseline creatinine are more susceptible to AKI and less likely to recover from those episodes of AKI . Second, this increased susceptibility is potentiated by factors that lead to longer wait times, whereby patients who spend more time at risk for renal injury are most vulnerable to CKD.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…They are therefore more susceptible to episodes of AKI and are less likely to have the renal reserve to recover from these episodes. This is supported by previous studies that demonstrated that those with a higher baseline creatinine are more susceptible to AKI and less likely to recover from those episodes of AKI . Second, this increased susceptibility is potentiated by factors that lead to longer wait times, whereby patients who spend more time at risk for renal injury are most vulnerable to CKD.…”
Section: Discussionsupporting
confidence: 61%
“…However, use of SLKT is highly variable, so this may not be the best metric to describe changes in the prevalence of CKD . This is critical because it is becoming more evident that pre‐LT CKD impacts the risk of both pre‐LT AKI and wait‐list mortality . That being said, although studies have investigated the impact of pre‐LT renal function on post‐LT survival, these studies were limited by subjective definitions of renal failure that did not distinguish between AKI and CKD .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As compared with patients without CKD, those with CKD were older and had significantly higher frequency of NASH‐related cirrhosis and diabetes mellitus. These results are in keeping with those from a recent study indicating that CKD in cirrhosis is common and that NASH as the etiology of cirrhosis with accompanying diabetes mellitus are risk factors to the development of CKD …”
supporting
confidence: 92%
“…Recent studies in hospitalized patients with cirrhosis indicate that chronic kidney disease (CKD) is common in this population, ranging from 20% to 46%. This is explained, at least in part, by the increase in the prevalence of nonalcoholic steatohepatitis (NASH)–related cirrhosis and associated comorbidities, such as diabetes mellitus and arterial hypertension . However, information on the burden of CKD in patients with cirrhosis is still limited.…”
mentioning
confidence: 99%